2020
DOI: 10.1136/flgastro-2019-101294
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and adverse factors for endoscopic mucosal resection (EMR) of colorectal polyps in elderly patients

Abstract: IntroductionEndoscopic mucosal resection (EMR) is an invaluable technique, however it is associated with significant risks. In the elderly in particular, the long-term survival benefits of polyp resection with EMR are unknown. The aim of this study was to determine the long-term outcomes in elderly patients who had undergone EMR and to identify any adverse factors.MethodA retrospective observational study on patients of 75 years of age or greater, who underwent EMR of colorectal polyps, in a single tertiary ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
0
3
0
3
Order By: Relevance
“…There were 2 studies that compared outcomes of EMR between patients older and younger than 80 years [ 11 , 12 ]. One study reported the outcomes of EMR in patients over 75 years of age, and one reported outcomes in patients over 80 years of age without a comparative group [ 10 , 14 ]. Two studies compared outcomes in patients older and younger than 75 years [ 13 , 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…There were 2 studies that compared outcomes of EMR between patients older and younger than 80 years [ 11 , 12 ]. One study reported the outcomes of EMR in patients over 75 years of age, and one reported outcomes in patients over 80 years of age without a comparative group [ 10 , 14 ]. Two studies compared outcomes in patients older and younger than 75 years [ 13 , 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…While the reasons underlying these trends are yet to be fully elucidated, specific changes in management of geriatric patients may play an important role. Recent work has demonstrated the safety and efficacy of endoscopic mucosal resection among this population [ 49 , 50 ]. Further, given the known complications of colectomy, higher surgical risk profile, and rapidly growing cohort of elderly patients, these patients may be referred at greater frequency for endoscopic intervention [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Сложность поставленной задачи состоит в различной стоимости медицинских технологий в разных странах, что не позволяет экстраполировать данные об эффективности затрат из одной страны в другую [31]. Так, в Австралии стоимость одного года продления жизни больным КРР благодаря скрининговым программам, составляет 16632$, в США -до 22000$, в Европе -до 5000$ [17,19,23]. Однако несомненная экономическая целесообразность скрининга КРР на данный момент не вызывает сомнений у специалистов США и большинства стран Европы [16].…”
Section: Discussionunclassified
“…Многие страны, в том числе Российская Федерация, выполняют рекомендации ВОЗ, приняв за формальное пороговое значение готовности платить денежное выражение, равное 1-3 показателям уровня валового внутреннего продукта (ВВП) на душу населения. В применении к данному критерию, целевая реализация скрининга КРР также демонстрирует результаты высокоэффективного экономического вложения [17,19,23].…”
Section: Volume IX Issue 6 2021unclassified
See 1 more Smart Citation